Differential effects of aerobic capacities on fight outcome in giant hissing cockroaches. (March 2021) - Mowles, Sophie L.; Skicko, Ian M.; Sturrock, Craig J.; Durrant, Kate L.
Abstract : When animals engage in contests, 'fights' are usually noninjurious, involving either signals or trials of strength. Such fights end once an individual assesses that it is the weaker opponent, or it has reached the threshold level of costs it is prepared to pay. We investigated the agonistic behaviours performed and the relative costs paid by winners and losers during aggressive interactions in two species of Madagascan hissing cockroaches (the wide-horned cockroach, Gromphadorhina oblongonota, and the flat-horned cockroach, Aeluropoda insignis ). By combining contest observations with measures of energetic expenditure and using X-ray computed tomography to compare the internal structure of the respiratory systems of the competitors, we revealed the differential physiological investment associated with resource-holding potential in these two species. Winners in G. oblongonota had larger respiratory volumes than predicted for their size compared to losers. Gromphadorhina oblongonota fought more aggressively and had larger respiratory systems overall than A. insignis, which engaged in less physical fighting. This indicates differential investment in fight tactics, and associated anatomy that may promote contest success. Invertebrate species at the upper limits of body size need to maintain efficient respiratory systems to support their size while also remaining subject to the influence of sexual selection. Highlights: Male hissing cockroaches compete over territories and access to fertilizations. Weaponry and contest dynamics vary between species in this tribe. X-ray CT scanning was used to compare the respiratory structures of competitors. Respiratory volumes were higher in dominants of the more competitive species. Sexual selection may act on respiratory anatomy that can promote contest success.